Whither Transverse Reinforcement in Bottle-shaped Struts?. (June 2018) - Singh, Bhupinder; Vimal, Abhishek; Gaurav, Govind
Abstract: Recommendations in many of the current design codes like the Eurocode and the AASHTO LRFD Bridge Design Code discount the effect of transverse reinforcement on strength of bottle shaped struts whereas the mechanics of the force system within a bottle-shaped strut suggests otherwise. In this investigation, the effect of amount of transverse reinforcement on strength of steeply inclined normal-strength and high-strength concrete bottle-shaped struts measured in terms of efficiency factors has been experimentally investigated for three transverse reinforcement ratios - 0.0031, 0.0046 and 0.0069, with the control bottle-shaped strut being transversely unreinforced. Efficiency factor increases of 31% and 25% in the normal-strength and the high-strength concrete bottle-shaped struts respectively were obtained when the transverse reinforcement ratio was increased from nil to 0.0031 whereas for the higher reinforcement ratios the increase in efficiency factor was relatively smaller. Service load crack widths in all the transversely reinforced struts were less than an upper bound value of 0.3 mm. The results of this investigation emphasise the role of transverse reinforcement in the strength of bottle-shaped struts and indicate that the 0.003 transverse reinforcement ratio recommended in the ACI 318-14 Building Code is the optimum amount of such reinforcement in normal-strength and high-strength concrete bottle-shaped struts.